2003
DOI: 10.3346/jkms.2003.18.4.473
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Soy Protein Hypersensitivity in Cow's Milk Protein-Sensitive Children in Korea

Abstract: This study was aimed to evaluate the prevalence of soy protein hypersensitivity in cow's milk protein-sensitive children in Korea. A total of 1,363 patients with atopic dermatitis, urticaria, enterocolitis syndrome, bronchial asthma or allergic rhinitis were recruited. First, we estimated the prevalence of sensitization to soy in children sensitized to cow's milk. Specific IgE levels > 0.7 kU/L by CAP assay were considered positive. Next, the prevalence of soy allergy in cow's milk allergy (CMA) patients was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
1
26
0
6
Order By: Relevance
“…Actually, a previous study also showed BLG has a weak cross‐reactivity with CNs . In addition, both cows' milk protein‐sensitised mice and cows' milk allergy patients shown that milk proteins had cross reactivity to soy protein . However, no cross‐reactivity existed between BLG and soy protein (Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Actually, a previous study also showed BLG has a weak cross‐reactivity with CNs . In addition, both cows' milk protein‐sensitised mice and cows' milk allergy patients shown that milk proteins had cross reactivity to soy protein . However, no cross‐reactivity existed between BLG and soy protein (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…36 In addition, both cows' milk protein-sensitised mice and cows' milk allergy patients shown that milk proteins had cross reactivity to soy protein. 37,38 However, no cross-reactivity existed between BLG and soy protein (Fig. 4C), indicating that the developed immunoassay was highly specific.…”
Section: Specificity Of the Fluorescent Selisamentioning
confidence: 93%
“…2,75,76 Soy formulas are often indicated when an infant is allergic to cow's milk; however, there is evidence that 8% to 14% of infants with cow's milk allergy are also reactive to soy formulas. 77,78 Ahn et al 79 studied the prevalence of soy protein hypersensitivity in children with cow's milk allergy; 18.3% of 224 children were found to have positive soy-specific IgE. Hydrolyzed formulas may be potentially useful for preventing allergic symptoms, but further studies are needed to evaluate this possibility.…”
Section: Hydrolysatesmentioning
confidence: 99%
“…The prevalence of a concomitant intolerance to soy in the allergy to cow milk is between 0% and 63% with high levels in the enterocolitis/enteropathy syndromes not associated with IgE (Van Sickle et al, 1985;Bock, Atkins, 1990;Ragno et al, 1993;Burks et al, 1994;Harikul et al, 1995). However, the true prevalence of allergy to soy proteins in documented allergies to proteins in cow milk is not yet well established (Kuitunen et al, 1975;Jakobsson, Lindberg, 1979;Zeiger et al, 1999;Ahn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%